Pengaruh Persepsi Harga dan Citra Merek terhadap Keputusan Pembelian Indomie Goreng pada Masyarakat Kelurahan Simpasai-Dompu - Nurul Fitratul Ramdani; M. Ikhwan Mansyuri; Risca Ariska Ramadhan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study was conducted to analyze the influence of price perception and brand image on purchasing decisions of Indomie Goreng products among the people of Simpasai Village. This study applied a quantitative method, with data collection techniques comprising observation, documentation, and questionnaire distribution. The sample consisted of 100 respondents selected using the incidental sampling technique. Data analysis was carried out through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination testing using the SPSS application. The results showed that price perception partially had a positive and significant effect on purchasing decisions with a significance value of 0.043 < 0.05. Brand image also partially had a positive and significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Simultaneously, price perception and brand image significantly influenced purchasing decisions. The coefficient of determination (R^2) was 0.169 or 16.9%, while the remaining 83.1% was explained by other variables outside this study